Socialization Of Usaha Soul Improvement through the Role of Waste Banks as UKM For Economic Drivers at The Al Azka Kamila Indonesia Foundation - Wahyu Kuncoro, Aris; Naryoto, Pambuko; Kristanto, Dwi; Hendrawan, Koen; Kasmawati, Yuni; Ipmawan, Hasan; Jusmanyah, Muhamad (Civil Officium: Journal of Empirical Studies on Social Science, 2022)
The waste problem is not only related to landfills, as has been the case so far, because the waste management system involves many parties, including waste producers (such as households, markets, institutions, industries, and others), managers (and contractors), regulators, the informal sector, and communities affected by waste management. Its completion requires the involvement of all relevant parties and various approaches. By looking at the above description, it is important to undertake counseling or socialization about the waste management system "Trash Bank" through community engagement, to find out how well this program works to reduce waste generation and turn waste into items of economic worth / Indirectly, this action will develop the Waste Processing Household Industry Group, organic fertilizer/compost, and create a healthy environment. With this PKM activity, it's intended that public awareness of the entrepreneurial spirit would grow. This service seeks to spread awareness and understanding of Waste Bank's waste management to promote a healthy and successful community. Improving school-community interactions (Budi Luhur University). Budi Luhur University's Tridharma community service program. Al Azka Kamila Indonesia Foundation: Increase knowledge, understanding, and entrepreneurial spirit in trash banks with commercial value. Develop the community's creative economy through reusing garbage. Increase awareness of the importance of a healthy environment. This community service was well-executed. Face-to-face or lecture training was given to the socializing committee. Al Azka Kamila Indonesia Foundation socialization resources on improving business spirit through waste banks as SMEs to drive the economy.